Forced Displacement, Exposure to Conflict and Long-Run Education and Income Inequality Evidence from Croatia and Bosnia and Herzegovina - Kovac, Dejan (The World Bank, 2022)
This paper investigates the long-term relationship between conflict-related migration and individual socioeconomic inequality. Looking at the post-conflict environments of Bosnia and Herzegovina (BiH) and Croatia, the two former Yugoslav states most heavily impacted by the conflicts of the early 1990s, the paper focuses on differences in educational performance and income between four groups: migrants, internally displaced persons, refugees, and those who did not move two decades after the conflicts. For BiH, the analysis leverages a municipality-representative survey (n = 6, 021) that captured self-reported education and income outcomes as well as migration histories. For Croatia, outcomes are measured using an anonymized education registry that captured outcomes for over half a million individuals over time. This allows an assessment of convergence between different categories of migrants. In both countries, individuals with greater exposure to conflict had systematically worse educational performance. External migrants now living in BiH have better educational and economic outcomes than those who did not migrate, but these advantages are smaller for individuals who were forced to move. In Croatia, those who moved during the conflict have worse educational outcomes, but there is a steady convergence between refugees and non-migrants. This research suggests that policies intended to address migration-related discrepancies should be targeted on the basis of individual and family experiences caused by conflict
Keywords: Access and Equity in Basic Education; Conflict; Education; Education Inequality; Educational Outcome Of Displaced Persons; Equity and Development; Forced Displacement; Income; Income Inequality; Inequality; Internally Displaced Persons (IDP); Macroeconomics and Economic Growth; Poverty Reduction; Refugee Inclusion; Refugees; Social Integration